GAYA KELEKATAN DAN KONSEP DIRI - Helmi, Avin Fadilla (Jurnal Psikologi, 1999)
This study was designed to examine the hypotheses that secure attachment was the best predictor of self-concept rather than unsecured attachment (anxious and avoidance attachments. Intercorrelation-matrix shows that there was positive correlation between secure attachment and self-concept (r = 0,522; p < 0,05) and negative correlation between unsecured attachment and self-concept (r= -0,500; p < 0,05). Keywords: attachment style, self-concept